A Study on Ethics In Advertising and Self Control: Exploring the Impact of Advertising on Consumer Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Advertising is explained as mass communication ofinformation intended to persuade buyers to buy products and with a view tomaximizing a company’s profits. Communication achieves the purpose of gettingone’s ideas across to the other party. But, more important purpose ofcommunication is to draw the desired response from the target audience.